Rozliczanie surowca w dwóch spółdzielniach mleczarskich na różne kierunki produkcji - Bazydło, Ignacy; Szczubełek, Grzegorz (Settlements of Raw Material Costs within Various Production Lines at Two Dairy Plants, 2005)
The amount of raw materials supplied to dairy plants each month is expressed in fat units and protein (plasma) units. This means that concentration of fat and protein is determined in raw materials purchased from particular suppliers. The results presented in this paper concern two dairy cooperatives, and a plant within the structure of one of the cooperatives At these dairies raw materials were allocated for production according to various programs corresponding to three production lines, namely: products for which there are no standards on levels of milk solids non-fat or protein, products for which protein content is determined, and products for which solids non-fat content is determined. This is out of question that dairies account for the amount of fat supplied and contained in finished products, but more and more attention is also paid to non-fat components of milk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 45-49